Carbyne bundles for a lithium-ion-battery anode - Park, Minwoo; Lee, Hoonkyung (Journal of the Korean Physical Society, 2013)
Carbyne, an infinite chain of sp-bonded carbon atoms, may be an effective material for energy storage applications, such as lithium-ion batteries, owing to its extremely large surface area (∼11000 m 2 g −1 ). Using first principles density functional calculations, we explored the possibilities of carbyne bundles for use in lithium-ion-battery anodes. A composite of a stable Li-intercalated carbyne bundle has the formula C 6 Li 13 . The open circuit voltage of the battery made with a carbyne bundle ranges from ∼0.3 to ∼0.9 V with changing concentration x (C 6 Li x ), meeting the voltage requirement for anodes. The Li-intercalated carbyne bundle (C 6 Li 13 ) possesses specific and volumetric capacities of ∼4840 mAh g −1 and ∼2038 mAh cm −3 , respectively, which are much greater than the corresponding values for graphite of ∼370 mAh g −1 and ∼820 mAh cm −3 . We propose that carbyne bundles can serve as high-capacity lithium-ion-battery anodes.